Experimental study on unloading confining pressure deformation and damage failure of multi-source coal-based solid waste cemented backfill - Xiang HE; Longqiang WEI; Ke YANG; Tong ZHANG; Cun ZHANG; Zilong ZHANG; Yanjun CHEN (Meitian dizhi yu kantan)
ObjectiveThe preparation of multi-source coal-based solid waste into filling materials for interval strip filling mining is one of the important means of green coal mining. The deformation and failure law of multi-source coal-based solid waste cemented backfill during strip coal pillar mining directly affects the stability of the stope.MethodsFive typical solid wastes were mixed with cement to prepare cemented backfill. The conventional triaxial and constant axial pressure unloading confining pressure stress tests of backfill specimens were carried out. The stress-strain curves and failure characteristics of backfill under two stress loading paths were analyzed. The evolution law of deformation parameters with confining pressure during unloading confining pressure was explored, and the unloading damage mechanism and strength criterion of backfill were revealed. Results and Conclusions The results show that: (1) The backfill specimens show brittle failure characteristics in the conventional triaxial test. The cracks gradually develop and rapidly expand during failure. The brittle failure characteristics in the unloading confining pressure test are enhanced. The strain change value before the failure of the specimen is less than 6.5% of the failure. (2) In the process of unloading confining pressure, the volume deformation of the filling body specimen changes from compression to expansion, the deformation modulus decreases by 10% of the failure stage, and the Poisson’s ratio breaks through the elastic-plastic material limit of 0.5 when the specimen is destroyed. (3) The confining pressure difference ratio decreases linearly with the initial confining pressure, which indicates that the backfill is more likely to be destroyed under high confining pressure environment, and the evolution of damage factor D is highly synchronized with Poisson’s ratio. (4) The Mogi-Coulomb strength criterion is suitable for the triaxial test of backfill specimens under constant axial compression and unloading confining pressure. The unloading behavior has a weakening effect on the cohesion of the backfill, and has a strengthening effect on the internal friction angle. The research results provide a reference for the stability control of interval strip filling mining.